Produção de ifn-y em pacientes com hanseníase e em seus contactantes numa amostra populacional do município de Sobral-Ceará - Jesus, Luciano Augusto Oliveira de (2007)
Leprosy, which is caused by Mycobacterium leprae, is an illness of ample clinical and immunopathological spectrum. Its clinical manifestations are correlated with distinct immunologic form, varying from a vigorous immune response mediated by cells to M. leprae, with type 1 standard in the tuberculóide polar region, to an absence of specific cellular response to antigens of M. leprae in the lepromatous polar region, with predominance of type 2 response and exacerbations of humoral response. The capacity of whole M. leprae antigen to stimulate peripheral blood mononuclear cell (PBMC) in the IFN-y production was measured in leprosy patients and their household’s contacts, in the city of Sobral, state of Ceará. A total of 30 leprosy patients were used for the study, before start chemotherapy. The paucibacilary leprosy patient group consisted of eight polar indeterminate, ten polar tuberculóide, two borderline tuberculóide, and the multibacilary leprosy patient group consisted of ten lepromatous leprosy and two borderline lepromatous leprosy. The household contacts group consisted of sixty healthy individuals, consanguineous and non consanguineous. The whole M. leprae antigen stimulated IFN-y production in the PBMC of seven borderline tuberculóide/tuberculóide (DT/TT), three indeterminate form, two borderline lepromatous/lepromatous (DV/VV the DT/TT group produced IFN-y levels significantly higher than DV/VV group (Fisher Test, p=0,027). The IFN-y production in the household contacts was observed in 34, 21 consanguineous and 13 non consanguineous. It wasn’t observed significant difference between paucibacilary household’s contacts (DT/TT, indeterminate form) and multibacilary household’s contacts groups in the IFN-y production to whole M. leprae antigen. However, it was observed significant difference in the production of these cytokine between household contacts and DV/VV patients. This study suggests that there wasn’t significative difference in the production IFN-y between non consanguineous and consanguineous subjects of the paucibacilary and multibacilary cases. Moreover, at correlacionated the production in these cytokine in the subjects with the presence of scar, we didn’t observed significative difference too.